2013
DOI: 10.1080/17470218.2012.754911
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of a visual-to-auditory sensory substitution device using interactive genetic algorithms

Abstract: Sensory substitution is a promising technique for mitigating the loss of a sensory modality. Sensory substitution devices (SSDs) work by converting information from the impaired sense (e.g., vision) into another, intact sense (e.g., audition). However, there are a potentially infinite number of ways of converting images into sounds, and it is important that the conversion takes into account the limits of human perception and other user-related factors (e.g., whether the sounds are pleasant to listen to). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In soundscapes generated from images, in contrast to western music, there is a tendency for adjacent frequencies to be played together. Using a semitone western scale would then generate sounds that are perceived as highly dissonant (Wright et al, 2013). Therefore, to generate more pleasant soundscapes, we used the pentatonic musical scale, which is a subset of the western musical scale (See supplementary materials) that generates less dissonance when adjacent notes are played together.…”
Section: Technical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In soundscapes generated from images, in contrast to western music, there is a tendency for adjacent frequencies to be played together. Using a semitone western scale would then generate sounds that are perceived as highly dissonant (Wright et al, 2013). Therefore, to generate more pleasant soundscapes, we used the pentatonic musical scale, which is a subset of the western musical scale (See supplementary materials) that generates less dissonance when adjacent notes are played together.…”
Section: Technical Descriptionmentioning
confidence: 99%
“…This was done because sounds with high energy in the 2500-5000 Hz range have been linked with unpleasantness (Kumar et al, 2008). In addition, a recent experiment investigating the perceived pleasantness of various SSD frequency ceilings showed that a ceiling of 2,500 Hz was selected as generating more pleasant soundscapes and a ceiling of 10,000 Hz was found to generate unpleasant soundscapes (Wright et al, 2013).…”
Section: Technical Descriptionmentioning
confidence: 99%
“…Rather, I simply wish to question the choice of the tactile modality as the pre ferred mode of information transfer. Indeed, I remain much more opti mistic about sensory substitution and augmentation systems that utilize the auditory modality (e.g., Meijer, 1993;Wright and Ward, 2013). Here I would like to concur with the line taken by Loomis et al (2012) regarding the very modest progress seen when it comes to general-purpose sensory substitution systems when compared to the much more successful uptake of specific-purpose sensory substitution devices.…”
Section: Notesmentioning
confidence: 57%
“…One might imagine a future in which AI could dynamically adjust the sonic expression of a brand to fit a listening environment or context, personalizing the advertising experience of a consumer (Maroely & Munichor, 2023; Suchman, 2024), or the potential for genetic algorithms to participate in the creation of sonic assets built on the crossmodal correspondences (cf. Wright & Ward, 2013). It has also been suggested that computational models may soon be able to predict perceived musical expression in branding scenarios (Lepa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%